Economic-financial evaluation of a cement company: Cementos Pacasmayo - Lizarzaburu Bolaños, Edmundo (2023)
Purpose: The aim of this paper is to address a company valuation procedure by explaining the steps that must be followed from an economic-financial perspective. Design/methodology: We employ the study case methodology to fulfill all the procedure stages. Specifically, we analyze the Peruvian cement company “Cementos Pacasmayo”. A 10-year discounted cash flow (DCF) is presented and brought to present value using a discount rate (WACC) composed by the cost of debt and the cost of capital of the company. Findings: We can conclude that the evaluation process should always include the country, industry and company. Practical implications: Our study provides useful implications for management. On the one hand, it is important to highlight the subjectivity to predict some parameters or doing assumptions. On the other hand, it is important to understand and know a good procedure to valuate a company as an insider or a potential investor. Originality/value: The proposed model consists of the economic studies of the country, sector and company, which allow the appraiser to specify certain parameters or assumptions for the elaboration of a model that approximates the value of the company.